Defining thyrotropin-dependent and -independent steps of thyroid hormone synthesis by using thyrotropin receptor-null mice - Marians, R. C. (National Academy of Sciences, 2002)
The thyrotropin (TSH) receptor (TSHR) is a member of the heterotrimeric G protein-coupled family of receptors whose main function is to regulate thyroid cell proliferation as well as thyroid hormone synthesis and release. In this study, we generated a TSHR knockout (TSHR-KO) mouse by homologous recombination for use as a model to study TSHR function. TSHR-KO mice presented with developmental and growth delays and were profoundly hypothyroid, with no detectable thyroid hormone and elevated TSH. Heterozygotes were apparently unaffected. Knockout mice died within 1 week of weaning unless fed a diet supplemented with thyroid powder. Mature mice were fertile on the thyroid-supplemented diet. Thyroid glands of TSHR-KO mice produced uniodinated thyroglobulin, but the ability to concentrate and organify iodide could be restored to TSHR-KO thyroids when cultured in the presence of the adenylate cyclase agonist forskolin. Consistent with this observation was the lack of detectable sodium-iodide symporter expression in TSHR-KO thyroid glands. Hence, by using the TSHR-KO mouse, we provided in vivo evidence, demonstrating that TSHR expression was required for expression of sodium-iodide symporter but was not required for thyroglobulin expression, suggesting that the thyroid hormone synthetic pathway of the mouse could be dissociated into TSHR-dependent and -independent steps.